PCSK9 in acute coronary syndrome: analysis of associations with clinical and laboratory characteristics - Yu. A. Drenina; K. Yu. Nikolaev (Кардиоваскулярная терапия и профилактика, 2020)
The article discusses a literature review reflecting the importance of identifying novel biomarkers in cardiology for improving conventional methods for diagnosing and stratifying risk in patients with acute coronary syndrome (ACS). Recently, more and more studies have published on such markers, in particular, on the proprotein convertase subtilisin/ kexin type 9 (PCSK9). The aim of this review was to analyze the associations of PCSK9 with clinical and laboratory parameters in patients with ACS. It has been demonstrated that the PCSK9 level in acute myocardial infarction is significantly increased. In patients with ACS, the level of PCSK9 is directly related to the duration of pain, the severity of coronary artery disease, familial hypercholesterolemia and lipid parameters, as well as the severity of coronary atherosclerosis according to the SYNTAX score. It was found that statin therapy before ACS significantly affects the association of PCSK9 with lipid profile. There are conflicting data on the associations of PCSK9 with the parameters of inflammatory response in ACS, as well as isolated evidence of the positive role of anti-IL-6 receptor monoclonal antibodies in ACS patients with dyslipidemia. The impact of PCSK9 on ACS prognosis is currently unstudied.